Retention of Fissure Sealants Used with Enamel and Dentin Bonding Agents - Hamid Moradian; Asiyeh Zohrei; Bahareh Shayeghi; Vahid Mehrabi (Islamic Dental Association of Iran, 2014)
Background and Aim: Tooth decay is the most common chronic disease. Fissure sealant therapy is among the suitable treatments to prevent occlusal caries. The ability of fissure sealant to prevent pit and fissure caries is due to the sealant retention. Considering the fact that several bonding agents are available in the market, clinical studies are required to assess the durability of sealants after using bonding agents. The purpose of this study was to compare the durability of fissure sealants bonded with dentin and enamel bonding agents after 12 months. Materials and Methods: A total of 30 healthy 6 to 12 year-old patients presenting with at least one caries-free, fully erupted molar tooth at each side of their mandible were select-ed. All fissures of 60 molars were sealed using the following two techniques: Group1: acid etchant + Single Bond (3M, ESPE) dentin bonding agent +Eco-S (VERICOM) group 2: acid etchant + Margin Bond (Coltene/Whaledent AG) enamel bonding agent +Echoseal sealant. Cotton roll isolation was used in both groups. Sealants were evaluated 12 months after placement. Data were analyzed using Wilcoxon test. Results: There was no significant difference between the two examined groups. Clinical success was 60% in group 1(dentin bonding agent) and 56.66% in group 2 (enamel bond-ing agent). Conclusion: Although no significant difference was found between the two groups, it seems that bonding agents with hydrophilic groups show more favorable results especially when appropriate isolation is not achieved.